TECHNOLOGY'S ROLE IN LANGUAGE TEACHING - RIDWAN RAMADHAN (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2023)
The integration of technology into language teaching has revolutionized traditional pedagogical approaches and reshaped the landscape of language learning. This paper examines the multifaceted impact of technology on language education, elucidating its contributions to engagement, accessibility, and efficacy in language acquisition. By harnessing a wide array of digital tools, platforms, and applications, educators can create immersive and dynamic learning experiences that cater to diverse learning styles and preferences.